The WT1-like transcription factor Klumpfuss maintains lineage commitment of enterocyte progenitors in the Drosophila intestine - Jerome Korzelius (Nature Portfolio, 2019)
Notch signaling mediates intestinal enteroblast specification in Drosophila but the molecular mechanism as to how this is regulated is unclear. Here, the authors show that the transcription factor Klumpfuss ensures enteroblast commitment through repression of enteroendocrine cell fate downstream of Notch.